2003
DOI: 10.1038/sj.mp.4001274
|View full text |Cite
|
Sign up to set email alerts
|

Atopy and depression: results from the Northern Finland 1966 Birth Cohort Study

Abstract: Several studies have suggested an association between IgE-mediated atopic allergies and depression. The present study extends our understanding about putative gender differences of this association and provides further epidemiological evidence for our previous finding that the association between atopy and depression may be characteristic for females only. In order to clearly determine the presence of atopic disorders and depression, we used more valid tools than had been employed earlier and we had access to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
80
4
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(101 citation statements)
references
References 61 publications
15
80
4
1
Order By: Relevance
“…50,51 Of interest, an association between depression and atopy has been recently reported in the Northern Finland 1966 Birth Cohort. 52,53 It is noteworthy that CRHR1 has a key role in inflammation, 54,55 and that CRHR1 antagonists, which have been used to treat depression, 34,35 also suppress peripheral inflammation. [56][57][58] Antidepressants are known to modulate inflammatory responses after chronic administration, in a time course that is reminiscent of the time frame of antidepressant effects and they also confer protection against cytokine-induced depressive-like biological and behavioral changes.…”
Section: Discussionmentioning
confidence: 99%
“…50,51 Of interest, an association between depression and atopy has been recently reported in the Northern Finland 1966 Birth Cohort. 52,53 It is noteworthy that CRHR1 has a key role in inflammation, 54,55 and that CRHR1 antagonists, which have been used to treat depression, 34,35 also suppress peripheral inflammation. [56][57][58] Antidepressants are known to modulate inflammatory responses after chronic administration, in a time course that is reminiscent of the time frame of antidepressant effects and they also confer protection against cytokine-induced depressive-like biological and behavioral changes.…”
Section: Discussionmentioning
confidence: 99%
“…A longitudinal association between asthma and subsequent hospitalization for schizophrenia, and adult diagnoses of depression has been reported (Timonen et al 2003;Pedersen et al 2012;Sanna et al 2014), and three longitudinal studies have reported increased rates of bipolar disorder in individuals with asthma (Liang & Chikritzhs, 2013;Chen et al 2014;Lin et al 2014). IL-6, C-reactive protein (CRP) and other inflammatory markers are associated with asthma and eczema (Takemura et al 2006;Arif et al 2007;Rincon & Irvin, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Klokk et al (30) studied the relationships between total and allergen-specifi c IgE and symptoms of anxiety and depression in women. Unlike Timonen et al (28,29), they did not fi nd any association between depression/anxiety and IgE levels.…”
mentioning
confidence: 55%
“…When the subjects were also categorised according to the severity of depression symptoms (29), the authors observed a higher proportion of diagnosed depressions in women with a positive prick test and suffering from allergic symptoms than in women with a negative skin prick test and without allergy symptoms irrespective of depression severity. In men, however, this association was found only in subjects having the most pronounced symptoms of depression (29). Klokk et al (30) studied the relationships between total and allergen-specifi c IgE and symptoms of anxiety and depression in women.…”
mentioning
confidence: 89%
See 1 more Smart Citation